Analysis of consumer perceived needs of fiber arts and crafts in the internet era with perceptual engineering as an orientation - Wang, Na; Zainal Abidin, Sazrinee; Shaari, Nazlina; Mansor, Noranita (Sciendo, 2024)
Starting from the construction of the perceptual engineering model, this paper gives the research objective of consumer perceived demand for fiber art handicrafts in the Internet era and designs the corresponding perceived SD scale according to consumer perceived demand. Factor analysis, the results show that for embroidery handicrafts, more attention is placed on grad in consumer perceived needs, with a factor loading eigenvalue of 4.647, and the grade variability of embroidery handicrafts is 27.336. The consumer perception under the cluster 1 category of handmade blankets is mainly the grade, and its percentage is the highest at 26.698, and the influence factor of style in bamboo and grass woven products is the highest at 23.078. The design of fiber art handicrafts oriented to perceptual engineering needs to fully explore the consumer's perception needs in order to promote innovation and development of fiber art handicrafts.